2008
DOI: 10.1111/j.1349-7006.2008.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐derived tumor necrosis factor‐alpha promotes progression and epithelial‐mesenchymal transition in renal cell carcinoma cells

Abstract: Pro-inflammatory cytokines and chemokines are involved in promoting tumorigenesis by facilitating tumor proliferation and metastasis. The serum levels of interleukin (IL)-6, IL-1β β β β, and tumor necrosis factor-alpha (TNF-α α α α) are significantly elevated in patients with renal cell carcinoma (RCC). However, the mechanisms of how these cytokines participate in the progression of RCC remains unknown. In the present study, we investigated the effects of tumorderived cytokines on invasion and the epithelial-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
98
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 36 publications
3
98
0
4
Order By: Relevance
“…These growth factors derived from RCC may be responsible for the constitutive activation of Akt. In addition, TNF-a is also secreted by tumor-associated inflammatory cells and RCC (17). TNF-a stimulated activation of PI3K/Akt and further enhanced tumor progression in RCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These growth factors derived from RCC may be responsible for the constitutive activation of Akt. In addition, TNF-a is also secreted by tumor-associated inflammatory cells and RCC (17). TNF-a stimulated activation of PI3K/Akt and further enhanced tumor progression in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a, a major mediator of cancer-related inflammation, can induce generation of different types of mediators, including reactive oxygen intermediates, cyclooxygenase, MMPs, and cytokines (6). RCC cells with mutated von Hippel-Lindau (VHL) and high malignant potential (2, 3) were found to produce increased low-level of TNF-a secretion ($10 pg/mL cells) (5,17,23). Coexpression of TNF-a and its receptors in RCC cells results in autocrine-and/or paracrine-stimulated growth (8,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive array of early reports indicated that TNF had oncolytic and antiproliferative effects in RCC [17][18][19]. However, later studies have cast this cytokine, which is secreted by immune and tumor cells, as an immunosuppressive mediator that promotes RCC progression [20][21][22]. TNF has thus been reported to kill T cells isolated from patients with metastatic RCC but not T cells from healthy donors and to inhibit CD81 T cells through the induction of programmed death ligand 1 on RCC cells [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a exhibits potent pro-angiogenic activity and stimulates tumour angiogenesis 40 , which is essential for tumour growth and invasion. TNF-a induces EMT transition in epithelial carcinomas and thus promotes tumour invasion 41 , and promotes tumour invasion by activation of MMPs such as MMP9 (ref. 42).…”
Section: Discussionmentioning
confidence: 99%